Analisis Formalin Secara Kualitatif pada Bakso dan Mie Basah di Kecamatan Sukarame, Wayhalim, dan Sukabumi: Qualitative Formaline Analysis on Meatball and Wet Noodle in Sukarame, Wayhalim, and Sukabumi - Riri Fauziyya; Anjar Hermadi Saputro (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Meatballs and wet noodles are foods that are favored by the community. The high water content causes these two types of food to be vulnerable and easily damaged in storage. The addition of chemicals such as preservatives in the manufacture of food products is carried out by producers so that the products are more durable, economical, and produce maximum profit. One chemical that is often misused for food preservatives is formaldehyde. Formalin is a dangerous chemical that is carcinogenic, mutagenic, corrosive, and irritating. This study aims to determine whether there is formalin content in meatballs and wet noodles that are sold in the districts of Sukarame, Wayhalim, and Sukabumi. This research was conducted in a qualitative analysis using Schiff's reagent on 30 samples of meatballs and 30 samples of wet noodles which were sold in Sukarame, Wayhalim, and Sukabumi. The results showed that 10 samples of meatballs and 2 wet noodles showed positive results containing formaldehyde. This shows that around 33.3% of the meatball sample and 6.66% of the wet noodles sample analyzed were identified to contain formaldehyde so that they are not safe for consumption in the long term and people must be careful in selecting meatballs and wet noodles for consumption. Keywords: Qualitative analysis, formalin, meatballs, wet noodles